2023
DOI: 10.1007/s42380-023-00174-w
|View full text |Cite|
|
Sign up to set email alerts
|

School Bullying and Personality Traits from Elementary School to University

Abstract: This retrospective study examines involvement in school bullying at all developmental stages, from elementary school to university, in relation to personality traits. Participants were 216 university students, 162 (75.0%) females and 54 (25.0%) males. The majority of the sample (88.9%) aged 18–24. Students completed the International Personality Items Pool (BFFM) and a self-report questionnaire about school bullying online. The results show that the involvement roles in personality trait A3 (don’t insult) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
0
0
Order By: Relevance
“…Our findings suggest the importance of considering the predictive role of specific personality traits in planning bullying awareness‐raising and prevention interventions. This perspective aligns with a recent studies (Gkatsa, 2023; Strohmeier et al, 2023) which investigated the relationship of personality traits with all roles of active involvement in school bullying, from primary school to university, proposing interventions that take into account specific personality traits as targets. The present study could offer new insights on traits to be considered for interventions involving adolescents, specifically for males and females.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our findings suggest the importance of considering the predictive role of specific personality traits in planning bullying awareness‐raising and prevention interventions. This perspective aligns with a recent studies (Gkatsa, 2023; Strohmeier et al, 2023) which investigated the relationship of personality traits with all roles of active involvement in school bullying, from primary school to university, proposing interventions that take into account specific personality traits as targets. The present study could offer new insights on traits to be considered for interventions involving adolescents, specifically for males and females.…”
Section: Discussionsupporting
confidence: 81%
“…Considering the five‐factor model of personality, a meta‐analysis (Mitsopoulou & Giovazolias, 2015), carried out on a sample of 21 studies, showed that lower levels of Agreeableness and Conscientiousness and higher levels of Neuroticism and Extraversion were associated with both bullying and victimization. Other later studies (Gkatsa, 2023; Jegede et al, 2022) suggested the associations between bullying perpetration and victimization and the Big Five personality inventory, confirming the meta‐analysis results. In addition, some authors (Volk et al, 2018), using the HEXACO (Honesty‐Humility, Emotionality, eXtraversion, Conscientiousness, Openess to experience) model of personality, showed that the low Honesty‐Humility factor represents the strongest predictor of bullying, followed by low Agreeableness and low Emotionality.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation